Metodologia para avaliação de falhas múltiplas em sistemas críticos visando o aumento da segurança - Demenech, Douglas (2018)
Providing security and reliability are fundamental to the development of critical systems projects. With the continual increase in the complexity of critical systems security projects, a search for new and more advanced analytical techniques occurs because it is necessary to ensure that the unwanted consequences are highly improbable. In general, this process is performed through computational simulations involving several operating scenarios and failures, having as main limitation the impossibility of representing all the paths of evolution of the system under analysis. In this work occurs the study and development of methodologies that support the proposition and validation of proposals of maintainability of critical systems able to raise the level in the area of analysis of safety and reliability. The proposed approach integrates Modeling and Formal Verification techniques as tools to support the design, analysis and implementation of maintenance strategies, mainly in order to verify if the strategy meets the safety requirements. The methodology consists of the verification of properties described in discrete and continuous temporal logics under an appropriate abstraction (formalism) of the behavior of the critical system and evaluation of the increase of the availability of the system with the implementation of maintenance proposals, that is, the study and development of a maintainability methodology that allows the proposal and validation of maintenance approaches in critical systems based on the formal verification technique, aiming to increase the reliability of these systems using discrete and hybrid temporal automata to represent them.